'Army of Cars': The automobile in Flora Gomes' The Blue Eyes of Yonta. (1st April 2013) - Teversham, Edward
This article explores Flora Gomes' use of the automobile as a visual trope in his seminal film The Blue Eyes of Yonta (1991). It is argued that the automobile is an essential component in the meaning and structure of the film. This 'automobility' is compared to the high levels of pedestrianism in Gomes' other work, as well as the role that the automobile has played within recent Guinean history. By considering the car both as a functional presence in the film as well as a more figurative object, it is observed that the automobile inhabits various spaces in The Blue Eyes of Yonta: social, cultural and political. The result is that Gomes uses the car as a multifaceted metaphor that encourages the viewer to reconsider how we incorporate the modern into our everyday behaviour.